2023
DOI: 10.3389/fvets.2023.980187
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antiviral activity of monolaurin against Seneca Valley virus

Abstract: IntroductionSurveillance of the Seneca Valley virus (SVV) shows a disproportionately higher incidence on Chinese pig farms. Currently, there are no vaccines or drugs to treat SVV infection effectively and effective treatment options are urgently needed.MethodsIn this study, we evaluated the antiviral activity of the following medium-chain fatty acids (MCFAs) or triglycerides (MCTs) against SVV: caprylic acid, caprylic monoglyceride, capric monoglyceride, and monolaurin.ResultsIn vitro experiments showed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Across the two independent sets of experimental data, it should be emphasized that the effect of GML on reducing ASFV infectivity in both strains is quite high. For SVV, it has been reported that GML treatment yielded a maximum reduction of only ~80% in in vitro experiments, yet still resulted in good in vivo performance in a porcine model in terms of reducing clinical symptoms, viral loads, and organ damage as well as promoting positive inflammatory responses [25]. GML exhibited a similar inhibitory effect on PRRSV, with around 80% reduction in viral infectivity in vitro [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the two independent sets of experimental data, it should be emphasized that the effect of GML on reducing ASFV infectivity in both strains is quite high. For SVV, it has been reported that GML treatment yielded a maximum reduction of only ~80% in in vitro experiments, yet still resulted in good in vivo performance in a porcine model in terms of reducing clinical symptoms, viral loads, and organ damage as well as promoting positive inflammatory responses [25]. GML exhibited a similar inhibitory effect on PRRSV, with around 80% reduction in viral infectivity in vitro [36].…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we evaluated the antiviral properties of glycerol monolaurate (GML) against the virulent ASFV Armenia/07 strain in order to validate the potential antiviral efficacy of GML against circulating, wild-type ASFV strains. GML is a regulatory acceptable, foodgrade monoglyceride that disrupts phospholipid membranes and has shown antiviral efficacy against a wide range of enveloped viruses, including in vivo treatment effects to ameliorate PEDV and Seneca Valley virus (SVV) infections in pigs [24,25]. Of note, GML has previously been shown to abrogate non-virulent ASFV BA71V strain infectivity in drinking water and had a higher level of antiviral activity than other tested medium-chain fatty acids [20].…”
Section: Introductionmentioning
confidence: 99%
“…Our study observed that dietary supplementation using benzoic acid and 1-monolaurin reduced serum IL-1β and ET levels in weaned piglets. This may correlate with 1-monolaurin's ability to enhance antiviral activity and inhibit inflammatory factor release [29]. In vivo studies deciphered that monolaurin supplementation alone in piglets decreased intestinal pathological damage and IL-8 and TNF-α levels, improving growth performance [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that dietary supplementation with benzoic acid and 1-monolaurin reduced serum IL-1β levels and serum ET levels in weaned piglets. This may be related to MLG-1's ability to enhance viral inhibitory activity and reduce the release of in ammatory factors [27]. In vivo studies have found that GML supplementation alone in piglets reduced intestinal pathological damage and levels of in ammatory factors IL-8 and TNF-α, thereby improving growth performance [28].…”
Section: Discussionmentioning
confidence: 99%